2017
DOI: 10.3390/ijgi6030065
|View full text |Cite
|
Sign up to set email alerts
|

Linking Neighborhood Characteristics and Drug-Related Police Interventions: A Bayesian Spatial Analysis

Abstract: Abstract:This paper aimed to analyze the spatial distribution of drug-related police interventions and the neighborhood characteristics influencing these spatial patterns. To this end, police officers ranked each census block group in Valencia, Spain (N = 552), providing an index of drug-related police interventions. Data from the City Statistics Office and observational variables were used to analyze neighborhood characteristics. Distance to the police station was used as the control variable. A Bayesian ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Police officers completed an index based on their perceptions and experience (objective records were not available), which comprised five items on a 5‐interval scale (where 0 = very low, and 4 = very high) including interventions such as drug‐related crimes, public drunkenness and fights, vandalism, homeless people, and truancy. Senior police officers with a thorough knowledge of the area were selected to score each item in each census block group (Marco, Gracia, & López‐Quílez, ). Cronbach's alpha was .74.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Police officers completed an index based on their perceptions and experience (objective records were not available), which comprised five items on a 5‐interval scale (where 0 = very low, and 4 = very high) including interventions such as drug‐related crimes, public drunkenness and fights, vandalism, homeless people, and truancy. Senior police officers with a thorough knowledge of the area were selected to score each item in each census block group (Marco, Gracia, & López‐Quílez, ). Cronbach's alpha was .74.…”
Section: Methodsmentioning
confidence: 99%
“…Cronbach's alpha was .74. In addition, this measure showed adequate validity properties because it was associated with neighborhood‐level variables related to concentrated disadvantage and disorder (Marco, Gracia, et al., ; Marco, Martín‐Fernández, Gracia, & López‐Quílez, ).…”
Section: Methodsmentioning
confidence: 99%
“…The posterior probability is considered to be a Bayesian counterpart of the p-value which is commonly used for evaluating the statistical significance of parameters in frequentist models [32,53]. To indicate parameter significance in this study, we followed previous research which have utilized the posterior probability of the parameter being different from zero (i.e., the posterior probability of the parameter being either positive or negative is greater than 90%) [54,55]. We found that the probability of being positive for EBF and THI was both higher than 90% and thus relevant to the response variable, specifically, p(β EBF > 0 O it ) = 91.6% and p(β THI > 0 O it ) = 99.7%.…”
Section: Spatio-temporal Analysismentioning
confidence: 99%
“…There are also two kinds of spatial factors, both designed based on a perpetrator's tendency to commit crimes in a familiar environment: (1) We account for the time and space factors of neighboring grids and make use of the neighborhood characteristics to make predictions [38]. In other words, given the diffuse nature of crime, there is a high likelihood that police activity in one crime-ridden area will push criminals into neighboring areas.…”
Section: Features Constructionmentioning
confidence: 99%